Classroom assessment: do teachers have the required competencies? - Abu Naim, Hamimah (2015)
This study investigated teachers' perceptions and competency in classroom assessment, and also examined mean differences on teachers' competency based on academic qualification, teaching experience and assessment training. A total of 367 teachers has been selected using random sampling technique among secondary schools in city zone Johor Bahru District. This study employed a survey design using a set of questionnaire consisted of 40 items with Likert Scale 5 point and value of Alpha Cronbach.90. Data were analyzed using descriptive (frequency, percentage, mean and standard deviation) and inferential statistical analysis (one way ANOVA). The findings showed that teachers have positive perception about classroom assessment (M=3.73; SD=.80) and overall teachers' competency in constructing classroom assessment (M=3.76; SD=1.04), where for planning (M=3.77; SD=.89), constructing (M=3.73; SD=.94), assembling (M=3.81; SD=.97), administering (M = 3.89; SD=1.42), scoring (M=3.77; SD=1.02) and item analysis (M= 3.56; SD=1.02). The study also found a significant mean difference on academic qualification (F=2.772, p